Pengaruh Rasio Keuangan Terhadap Return Saham: (Studi Empiris Pada Perusahaan Manufaktur Yang Listed Di Bursa Efek Indonesia Periode 2017-2020) - Khoriatulla Hafifin; Arik Susbiyani; Suwarno (CV. Ulil Albab Corp, 2022)
Analysis of financial ratios and stock prices can be used as an evaluation tool of the condition or existence of financial companies in the past, present and projecting future results, and can analyze 30 companies manufacturing the effect on stock returns. Where the financialstatement analysis can be done using with financial ratios. Ratios are used to assess the financial performance of companies such as liquidity ratios, leverage ratios, activity ratios, and profitability ratios, as well as stock prices. This study aims to analyze financial ratios and stock prices on stock returns, the study population was manufacturing companies listed on the Indonesia Stock Exchange Period 2017-2020. Samples has taken thirty manufacturing company. This type of research is descriptive statistics for this type of research related to the application of statistical methods for collecting, processing, and presentation of a group, the research data can be grouped in a secondary data. Methods of data collection in this research using observation, interviews, and literature studies. The analysis technique used is variable by testing the hypothesis or research explanation. The analytical tool used in this research is the analysis of the classical assumption, multiple linear regression analysis, the coefficient of multiple determination, t test and F test results showed that the debt-to-asset ratio (DAR) significant effect on stock returns. Current Ratio (CR) a significant effect on stock returns. return On Assets (ROE) significantly affects the profitability of the company. Total Assets Turn Over (TAT) has no significant effect on stock returns, and Price to Book Value (PBV) significant effect on stock returns.